Pengaruh Guided Imagery terhadap Tingkat Depresi pada Pasien Diabetes Melitus - Patrayana, I Made Tantri; Candra, I Wayan; Sumirta, I Nengah; Harini, I Gusti Ayu; Ari Kresna Dewi, Ni Luh Gede (Jurnal Gema Keperawatan, 2024)
Diabetes melitus is a dangerous health problem and is still listed as a cause of death in the world. Patients with diabetes melitus are at high risk of experiencing depression and ultimately worsening self-care. Therefore psychological treatment is carried out, one of which is guided imagery.The purpose of this study was to determine the effect of guided imagery on depression in diabetes melitus patients at UPTD Health Center I South Denpasar in 2023. This study used a pre-experimental  method with a one-group pre-post test design. The sampling technique used non-probability purposive sampling with a sample of 32 people. The research instrument used the Beck Depression Inventory-II (BDI-II).Data analysis technique using the wilcoxon signed rank test. The results showed that the level of depression in patients with diabetes melitus before being given guided imagery, most of the patients experienced moderate depression, 17 people (53,1%) then the level of depression in patients with diabetes melitus after being given guided imagery showed that most patients with diabetes melitus experienced mild depression, numbering 24 people (75.0%). After being analyzed, the results obtained were p-value = 0.003 (p 0.050). The conclusion of this study is that there is a significant effect of guided imagery on depression in diabetes melitus patients at UPTD Health Center I South Denpasar in 2023.